Victoria College catalogue of original paintings - Victoria College (B.C.). Fine Arts Committee. (Victoria College, 1955)
Front cover includes the inscription: It is the policy of the Fine Arts Committee to acquire original paintings by British Columbia artists, which will form the nucleus of a permanent collection of Canadian Art. Item consists of descriptions of works by British Columbia artists, which are amongst the significant early acquisitions by Victoria College's Art Committee. Artists are: Emily Carr, unidentified Eskimo (Inuit) artists, Bruno Bobak, Gordon Smith, Myfanwy Pavelic, Donald Jarvis, J.L. Shadbolt, J.F. Plaskett, Judith Morgan, W. P. Weston, and Lawren Harris. Undergraduate Unreviewed